Development of an LC-MS/MS method for astaxanthin quantification in shrimp tissues and its application to detect astaxanthin variations during ovary development stages - Diao, Shuo; Feng, Guanrong; Wang, Yixuan; Ma, Jingming; Lv, Zhihua; Yu, Mingming; Sun, Yue (Frontiers in Nutrition, 2025)
ObjectiveIn this study, a highly selective and sensitive LC-MS/MS method was developed to comprehensively analyze the distribution of astaxanthin across various tissues of Litopenaeus vannamei, as well as its variations in the hepatopancreas and ovary throughout ovarian development.MethodsThe separation was performed on a BEH C8 column (1.7 μm, 2.1 × 50 mm) using a a gradient elution. The initial mobile phase composition was 0.1% formic acid in 3 mM ammonium acetate in water (solvent A) and methanol (solvent B) at a ratio of 15:85 (v/v), with a flow rate of 0.20 mL/min.ResultsThe assay demonstrated linearity over a concentration range of 20 to 10,000 ng/mL, with accuracy varying from −0.1 to 1.7% and precision within 2.1%. Using the established methodology, astaxanthin concentrations were quantitatively analyzed and comparatively assessed across various tissues of L. vannamei. Analytical results demonstrated that the ventral nerve cord and hepatopancreas exhibited the highest astaxanthin concentrations among all examined tissues, with values of 351 μg/g and 116 μg/g, respectively. During the ovarian developmental stages, astaxanthin was predominantly sequestered in the hepatopancreas during early phases, with concentrations ranging from 21.3 μg/g to 29.1 μg/g, representing a 43- to 59-fold increase compared to ovarian concentrations. However, a significant redistribution of astaxanthin was observed during the post-developmental stage, characterized by a substantial decrease to 5.74 μg/g in the hepatopancreas, concomitant with an increase to 7.47 μg/g in ovarian tissue.ConclusionThis validated LC-MS/MS method effectively quantified astaxanthin in various tissues of Litopenaeus vannamei, providing new insights into its tissue-specific distribution and potential role during ovarian development.